The Role of Modern Youth in The New Uzbekistan - Asranov S.A. (Web of Journals Publishing, 2023)
Youth is the future of any society. In a literal sense, they are the greatest wealth and priceless treasure of Uzbekistan. After all, the youth of new Uzbekistan is the basis of our future and prospects.
Keywords: spirituality, people, personality, upbringing, tolerance, freedom.